2020
DOI: 10.1515/cclm-2020-1212
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of presepsin in patients with cirrhosis and bacterial infection

Abstract: ObjectivesSerum biomarkers have suboptimal accuracy for the early diagnosis of bacterial infection (BI) in cirrhosis.AimTo evaluate the diagnostic and prognostic accuracy of presepsin (PSP) in a cohort of hospitalized patients with cirrhosis.MethodsAll adult cirrhotics admitted between 03.2016 and 06.2019 were consecutively evaluated. PSP was measured using chemiluminescent enzyme immunoassay, and its accuracy was compared with that of common biomarkers.ResultsA total of 278 cirrhotic patients for a total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…In both cases, PSP had significant cutoff values at T0 and T1, as well as a high PSP level of more than 1000 pg/mL for ICU mortality. Previous studies hypothesized that PSP can be used not only to predict the potential occurrence of sepsis but also mortality [ 1 , 34 , 35 , 36 , 37 ]. Similarly, our study results demonstrated that PSP may play a pivotal role in predicting ICU and in-hospital mortality, as well as the onset of sepsis during early postoperative phase, even in patients with mild AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, PSP had significant cutoff values at T0 and T1, as well as a high PSP level of more than 1000 pg/mL for ICU mortality. Previous studies hypothesized that PSP can be used not only to predict the potential occurrence of sepsis but also mortality [ 1 , 34 , 35 , 36 , 37 ]. Similarly, our study results demonstrated that PSP may play a pivotal role in predicting ICU and in-hospital mortality, as well as the onset of sepsis during early postoperative phase, even in patients with mild AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Presepsin level in the liver may have been elevated without infection due to inflammation and fibrosis from underlying diseases [ 35 , 36 ]. Furthermore, presepsin level tends to increase with cirrhosis progression and renal dysfunction, even without infections [ 17 , 18 , 37 ]. Therefore, the reason for the increased level may be cirrhosis progression, hepatorenal syndrome, or potential inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with procalcitonin and CRP, presepsin is a superior diagnostic biomarker in terms of accuracy and detects infections in the earlier phase [ 12 , 13 , 15 , 16 ]. In patients with liver cirrhosis, presepsin level tends to increase with cirrhosis progression even without infection and is associated with survival rate [ 17 ]. Thus, the usefulness of presepsin for diagnosing infection in patients with liver cirrhosis who require LT is controversial [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different biological markers were tested over time to diagnose infections and/or sepsis in patients with LC [ 7 , 8 , 9 , 10 , 11 ]. C-reactive protein (CRP), procalcitonin (PCT), and presepsin are practical to be used in daily clinical practice and were evaluated in patients with different stages of LC as the markers of infections or sepsis [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%